2019
DOI: 10.1177/1932296818823728
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of the Artificial Pancreas: Comparing the Effect of Technology Readiness, Product Characteristics, and Social Influence Between Invited and Self-Selected Respondents

Abstract: Background: Psychosocial factors that may affect acceptance of artificial pancreas (AP) systems have been investigated in small sample sizes of highly motivated, self-selected persons with type 1 diabetes (T1DM) with a focus on product characteristics. We aimed to develop a valid survey to investigate the association of technology readiness and social influence with AP acceptance in a larger sample, including both self-selected and invited respondents with T1DM. Methods: An online survey was developed based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…Of the 902 respondents, 85.5% stated that they would trust such a system, whereas 8.0% (n = 84) would not, and another 8.0% saw no need for improvement in their current therapy. This finding is similar to previous surveys [ 25 ].…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…Of the 902 respondents, 85.5% stated that they would trust such a system, whereas 8.0% (n = 84) would not, and another 8.0% saw no need for improvement in their current therapy. This finding is similar to previous surveys [ 25 ].…”
Section: Resultssupporting
confidence: 94%
“…of DIYCL users compared to non-users in our survey corresponds to prior data must be assessed critically [25] Nevertheless, the result is positive, because a greater power was achieved with the DIYCL survey.…”
Section: Plos Onesupporting
confidence: 52%
See 2 more Smart Citations
“…Additionally, a recent study highlighted the findings that acceptance of an AP system depends more on a stronger bond of the users with product characteristics (such as usefulness, complexity and compatibility) than technology readiness (such as innovativeness and insecurity) 42. However, the researchers also concluded that the results differed between self-selected and invited persons, so researchers and product developers should be cautious when relying only on self-selected persons in the design, testing and development of AP systems.…”
Section: Discussionmentioning
confidence: 99%